Methods in fungal biology: A manual of laboratory protocols - Gautam, Ajay K.; Avasthi, Shubhi (Jodhpur: Scientific Publishers, 2025)
Fungi are one of the important components in the biosphere, ubiquitous in nature and essential in recycling of nutrients in all type of habitats. These organisms play key role as decomposers, phytopathogens, symbionts and in elemental cycles. Despite of their important roles in the biosphere, it is important to explore all categories of fungi. This manual is designed to provide detailed information on methods of fungal isolation and identification from various substrates. The book is comprised in three parts where first part contains information about instrumentation, techniques, stains, cultures and reagents; second part describe about fungal isolation and identification while, third part depicts about cryopreservation methods, safety norms and regulations in handling fungal specimens as well as about bibliography. Almost all the techniques used in isolation and identification of fungi from various substrates viz. soil, water, air, indoor environment, plant tissues, plant rhizosphere and stored materials are provided in complete detail. Identification keys of fungi are also covered and complied in this book. This book has complete basic information on experimental mycology which makes it useful for undergraduate, post graduate and beginners in this scientific and interesting field of fungal studies.
Part A: Instrumentation, techniques, stains, cultures and reagents ; Part B: Fungal isolation and identification ; Part C: Preservation, Safety norms and Appendix
includes appendix and Bibliography
Keywords: Fungal biology -- Methods -- Laboratory protocols